Estado nutricional y hospitalización por infección respiratoria aguda, en niños menores de 5 años, Punchana 2023 - Flores Panduro, Karina Giovanna (2025)
The objetive of the study was to determine the relationship between nutritional status and hospitalization for acute respiratory infections, in children under 5 years of age, at Hospital III EsSalud, Iquitos 2023. A non – experimental, cross – sectional, correlational quantitative method was used. The population included children under 5 years of age hospitalized in the pediatric service during the year 2023. The sample is made up of 97 hospitalized children, during the year 2023. The results found were: Of the total samples, 97 (100%) hospitalized children, 49 (50.5%) corresponded to the male sex and 48 (49.5%) to the female sex, the mean age of the children was 20.2 months, with a SD of 16.4 months, minimum age 1 month and maximum of 59 months, for a N of 97 hospitalized children, the average hospitalization days were 3.53 with a SD of 1.81 hospitalized days, minimum day 1 and maximum 12 days, for an N of 97 hospitalized children, 68 (88.3%) had normal birth weight and 1 (1.3%) was macrosomic, the mean age of the mother was 29.2 years old, with a SD of 4.56 years, minimum age 18 years and maximum age 39 years, for a total of 97 mothers of hospitalized children. A pplying the Mantel – Haenszel trend test, χ²3.26 df 1p< 0.08 was significant, leading to the conclusión that there is a relationship between nutritional status and acute respiratory infections.